Qualitative Proteomic Profiling of Saccharomyces cerevisiae E1 Strain During Alcoholic Fermentation of Yellow Passion Fruit: A First Approximation - Roger Consuegra-Rivera; Juan J. Román-Camacho; Inés M. Santos-Dueñas; Teresa García-Martínez; Juan Carlos Mauricio; Isidoro García-García (Foods)
Yellow passion fruit provides a substrate suitable for alcoholic fermentation and holds valuable sensory and nutritional properties that support its use for producing wine. Among the different interesting aspects to consider in the winemaking process, we highlight the analysis of the proteins of the yeast or yeasts responsible for the process; in addition to providing fundamental knowledge about the biotransformations that take place, they can contribute to understanding basic aspects that affect the sensory properties of the wine obtained. This study aimed to analyze the proteomic profile of the yeast Saccharomyces cerevisiae strain E1 (ATCC: MYC-425) during passion fruit fermentation. The process was conducted in a 5 L Sartorius bioreactor with a diluted fruit puree and sucrose, making a medium with a 10% v/v alcohol potential; after 4 days, ethanol reached 8.5% v/v as sugars decreased. Subsequent LC/MS-MS analysis allowed identifying a total of 938 valid proteins: 454 from the fruit substrate and 484 attributed to yeast. Of the latter, 243 proteins were present throughout the fermentation, with GO term analysis highlighting “binding” (78%) and “catalytic activity” (66%) in molecular function, as well as “cellular” (98%) and “metabolic (90%) processes” in biological process domains. These findings may be a significant step forward in understanding the proteomic dynamics of S. cerevisiae in tropical fruit fermentations. By revealing key proteins and their roles in the unique conditions of passion fruit must, this study offers insights for optimizing the wine elaboration procedures and improving organoleptic properties and quality.